The formalization of banking supervision: A comparison between Japan and Sweden - Eiji Hotori; Mikael Wendschlag (The European Association for Banking and Financial History (EABH), 2018)
This study examines the formalization of banking supervision in Japan and Sweden that occurred in the decades around 1900. Using an incremental change approach, the respective cases are traced and examined from three dimensions: 1) the legal framework, 2) the banking supervisory agency, and 3) bank supervisory activities. As a result of the comparative analysis, we find several similarities and differences. The most important finding is that the two cases are similar, in that financial crises - generally considered to be a primary driver for major regulatory and supervisory reforms - did not play the main role in the formalization of supervision in either Japan or Sweden. Rather, the formalization was an incremental adjustment to the organic development of the banking sector, the general public's increasing exposure to the banks as deposit holders and borrowers, and the increased need for professionalization of the banking sector.
Keywords: G18; G21; N20; N23; N25; N40; N43; N45; 330; banking supervision; formalization; incremental change approach